Time Management Analysis of the Construction of the Kali Tuan Dam Project in Indramayu Regency - Ibnu El Musayyab; Lulu Raudlatul Aulia; Heri Mulyono; Ohan Farhan (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Dams are structures designed transversally across rivers and play a role in increasing water elevation. This study discusses whether the construction of dams in Krimun Village , Indramayu has met the feasibility. The results of surveys and interviews with local communities were collected as primary data, while information from various sources such as literature , government documents, and climatology data are secondary data. The researcher chose a research method through literature studies, as well as data analysis. The finalization of this study showed that the CPM method adapted as the construction method for the Kali Tuan Dam obtained a time difference of 29 days. The calculation starts from the initial planning time with the CPM time. Initially, the estimated duration of this project was 120, but it turned out to be shortened to only 91 days. On the other hand, this accelerated duration has an impact on the project calculation costs which have increased from IDR 1,476,703,244.59 to IDR 1,523,841,512.45.